Novel thalidomide analogues, â€œme tooâ€ drugs and the Brazilian law - Francisco JosÃ© Roma Paumgartten (Fundação Oswaldo Cruz (FIOCRUZ), 2013)
In Brazil, thalidomide has been used virtually without interruption since it was launched as a new and revolutionary sedative drug in 1956. After 1965, when its efficacy to treat erythema nodosum leprosum (ENL) was discovered, it was regarded as an essential drug because the prevalence of Hansenâ€™s disease is high in the country. In the 1990s and thereafter myriad novel therapeutic uses for thalidomide (autoimmmune diseases, multiple myeloma, aphthous ulcers in AIDS, and others) have emerged owing to its immunomodulatory and antiangiogenic activities. Owing to a marked teratogenicity, however, the prescription and dispensing of thalidomide to patients is strictly controlled in Brazil and elsewhere. Notwithstanding the stringent regulations, a number of post-1965 cases of thalidomide embryopathy have occurred in Brazil. In 2003, a federal law (Law 10.651/2003) prohibited the sale and dispensing of thalidomide in commercial pharmacies. The law, however, made no provision for teratogenic drug analogues such as lenalidomide and pomalidomide, which have been cleared for marketing in the USA, Europe and other countries. Although they are much more expensive than thalidomide, the clinical superiority of novel ana-logues over thalidomide in multiple myeloma and other conditions remains unproven. Therefore, so far novel analogues can be considered as thalidomide â€œme tooâ€ drugs. This author strongly recommends that an amendment to the current law prohibiting the sale and dispensing of thalid-omide in commercial pharmacies be extended to thalidomide analogues. Moreover, we consider that a demonstration of clinical superiority over thalidomide (through gold-standard comparative efficacy trials) should be an essential requirement for registration of any teratogenic analogue.